Dietary Intake of College Athletes in Tertiary Institutions in the North Rift Region of Kenya - Waititu , Lucy M.; Mugalavai , Violet K.; Serrem , Charlotte A. (African Journal of Education,Science and Technology (AJEST), 2013)
The concept that proper nutrition contributes to optimum performance is a widely accepted one and both the elite and college athlete aim at excelling in their performance. It was therefore necessary to determine the dietary intake of college athletes since they are the elite athletes of the future. The aim of the study was to determine the dietary intake of college athletes in tertiary institutions in the North Rift region of Kenya and compare this with recommended dietary allowances (RDA). A cross-sectional survey in the quantitative and qualitative paradigms was carried out in two technical training institutes. The study was guided by the Food Choice Process Model. A sample of 44 male and 27 female athletes, 18-26 years old was selected. Anthropometric measurements were taken to determine body mass index (BMI) and body fat percent. Micronutrient and macronutrient intakes were determined using the 7-day estimated food record. Food intake data was analyzed using Nutri-Survey software. Based on BMI, all athletes were classified as normal. Body fat percent was 6% for male athletes and 11.7% for female athletes which was lower than the standard body fat for athletes of 6%-13% and 14%-20% for males and females respectively. Diets of both male and female athletes consisted significantly lower than recommended daily intakes of energy, fat and water and the athletes were in negative energy balance. Vitamins C, folic acid, potassium and calcium intake were below RDA for both male and female athletes. Female athletes exhibited inadequate iron intakes. From the findings of the study, it was concluded that the diet of the college athletes was inadequate in energy and some micronutrients and this could put them at a risk of nutritional deficiencies and compromise their athletic performance. Poor performance in athletics would affect individual and national development. The study recommended that training institutions seek the services of qualified sports nutritionists to guide athletes in their choice of diet. It is also necessary to have nutrition education programs both for the athlete and the coach to train on basic nutrition for enhanced performance